Representasi Gaya Hidup Pada Iklan Galaxy Watch Active Dalam Website Kumparan - Odillia, Lisa; Marghantia, Shella Safera (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2023)
Technological development and communication affect the outcome of product functions. With changes in business technology, the human mindset also changes because users prefer something instant to support the comfort of life. In this analysis, a representation of smartwatches represents a minimalist modern life. In addition to supporting the appearance and utilizing technology, smartwatches offer benefits that make life healthy, easier and faster. The minimalist lifestyle is when someone limits ownership of goods and focuses on important needs in his life. The existence of a full-featured smartwatch provides opportunities for consumers to minimize the cost of purchasing communication devices, reducing consumption of health products and focusing on self-development.